Studies on the photoelectronic properties of a manganese (Mn)-doped lead-free double perovskite. Issue 41 (18th October 2022) - Xue, Shaoming; Wu, Qiaoqian; Huo, Qiuhong; Mi, Jun; Guan, ChengBo; Cong, Wei-Yan; Zhang, Zhenkui; Ren, Junfeng; Lu, Ying-Bo
Abstract : ELF calculations and COHP analyses confirm that the Cl–Mn bonds in the Cs2 AgInCl6 :Mn 2+ system exhibit more ionic characteristics and stronger bond strengths, which accounts for the blue-shift of the PL peak of Mn ions from Cs2 AgInCl6 to Cs2 NaBiCl6 . Abstract : Taking Cs2 NaBiCl6, Cs2 AgInCl6 and Cs2 AgBiCl6 as examples of lead-free double perovskites (DPs), we study the photoluminescence (PL) properties of Mn-doped DPs. The electron localization function (ELF) reveals the more ionic nature of the Na–Cl bond in Cs2 NaBiCl6 than that of the Ag–Cl bond in Cs2 AgBiCl6 . Bader charge calculations confirm the nominal +2 valence state of Mn ions in both DPs. Mn 2+ ions introduce two defect levels in the band gap of the Cs2 NaBiCl6 host, accounting for the d–d transition ( 4 T1 – 6 A1 transition) of Mn 2+ and thus the subsequent orange PL. The changes of the crystal field and their influences on the emission energy of Mn 2+ ions in different DPs are evaluated by calculating the Racah parameters ( B and C ) and the crystal field strength (Dq) obtained from energies of the terms of d 5 in the Cs2 NaBiCl6 :Mn 2+ and Cs2 AgInCl6 :Mn 2+ systems. The results show that Dq in Cs2 AgInCl6 :Mn 2+ is stronger than that in Cs2 NaBiCl6 :Mn 2+ . The analyses on bonding interactions of the Mn–Cl bond via ELF and the integrated projected pCOHP also confirm the stronger ionic bonding interactions and thus the boost of the crystal field strength in the Cs2 AgInCl6 :Mn 2+ system, which results in the blue-shift of the Mn 2+ introduced PL peak from Cs2 AgInCl6 to Cs2 NaBiCl6 . Our results provide a new strategy to modulate the emission wavelengths, i.e., tuning the crystal field.